0
$\begingroup$

How to convert a formula from DNF to CNF. Example:

$(A \wedge \neg B) \vee (B \wedge \neg A)$ or similar trivial DNFs? It thought it could be work with the distributive law. But I don't know how to continue from: $(A \vee ( B \wedge \neg A)) \wedge ( \neg B \vee (B \wedge \neg A))$

Thanks for help!

$\endgroup$
2
$\begingroup$

$$A \lor (B\land \lnot A) = (A \lor B) \land (A\lor \lnot A) = A \lor B$$ and $$\lnot B \lor (B \land \lnot A) = (\lnot B \lor B) \land (\lnot B \lor \lnot A) = \lnot B \lor \lnot A$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.